2016
DOI: 10.1007/s12034-016-1282-z
|View full text |Cite
|
Sign up to set email alerts
|

Growth and properties of lead iodide thin films by spin coating

Abstract: Abstract. In this study, lead iodide (PbI 2 ) thin films were deposited on glass substrates by spin coating a solution of 0.2 M PbI 2 dissolved in dimethylformamide, varying the deposition time and the spin speed. The thickness of the thin films decreased with increase in spin speed and deposition time, as examined by profilometry measurements. The structure, morphology, optical and electrical properties of the thin films were analysed using various techniques. X-ray diffraction patterns revealed that the thin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…Thin films of MAPbI 3 and PbI 2 were deposited onto quartz substrates using standard solution-deposition protocols [2,41]. MAPbI 3 films were then annealed for 96 h (4 days) under ambient pressure N 2 , at temperatures of 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thin films of MAPbI 3 and PbI 2 were deposited onto quartz substrates using standard solution-deposition protocols [2,41]. MAPbI 3 films were then annealed for 96 h (4 days) under ambient pressure N 2 , at temperatures of 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C.…”
Section: Resultsmentioning
confidence: 99%
“…The lifetime as determined by TRMC depends on the carrier concentration, and hence the relative contribution from bimolecular and Auger recombination [44], but values in the range of a few 100 ns are common for polycrystalline MHP films at typical TRMC fluences [38,45]. Figure 2(c) shows an example transient of a film of lead iodide (PbI 2 ), prepared using previously reported solution-deposition protocols [41], and not subjected to extended annealing. PbI 2 is one of the main reported decomposition by-products of MAPbI 3 [46] and should possess some character of a fully-decomposed MAPbI 3 film.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, few less intense peaks around 25.74 and 38.88 are observed representing (011) and (110) orientations, respectively. [44] The diffraction angles for high-temperature annealed PbI 2 films are almost coincident with the PbI 2 film annealed at 70 C. The differences in the peak intensity and full width at half maximum (FWHM) values for the (001) orientation can be distinguished from the intensity-scaled diffraction patterns, as shown in Figure 1c. We observed that the peak intensity for PbI 2 -70 C is very weak with a broad FWHM value of 0.2791 .…”
Section: Morphological and Crystallographic Analysismentioning
confidence: 68%
“…The peaks located at 45, 81, 136, and 180 cm −1 originate from the Pb–I bond vibration, which are the characteristic modes of the perovskite crystal structure. Several authors have assigned these low wavenumber peaks to the modes of the inorganic cage in the perovskite crystal structure . However, the broad peaks located at 271 and 534 cm −1 are assigned to the organic component of the perovskite; they originate from the torsional modes of the methylammonium cation .…”
Section: Resultsmentioning
confidence: 99%